2001
DOI: 10.1176/appi.ps.52.1.56
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Quality and Outcomes in Routine Depression Care

Abstract: This community-based, nonexperimental study found a positive relationship between the quality of care for depression and clinical outcomes for patients with major depression in routine practice settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 35 publications
2
35
1
Order By: Relevance
“…However, we recognize that future research needs to address challenges to the internal validity of these findings from selection bias and causal inference issues. In terms of selection bias (Newhouse & McClellan, 1998;Sturm, Unutzer, & Katon, 1999), our inability to use instrumented models in all likelihood downwardly biases the indicator-outcome relationships we report by an estimated 20% or greater (Fortney et al, 2001;Schoenbaum et al, 2002). In terms of inference, we recognize the non-experimental design prevents us from definitively concluding that high-quality depression care improves clinical outcomes; however, experimental studies showing that interventions that improve antidepressant medication management do in fact significantly reduce depressive symptoms (Wells et al, 2000;Rost, Nutting, Smith, Elliott, & Dickinson, 2002;Katon et al, 1995;Katon et al, 1996;Schulberg et al, 1996;Katzelnick et al, 2000;Katon et al, 1999;Simon, VonKorff, Rutter, & Wagner, 2000;Hunkeler et al, 2000), strengthen the causal link between quality and outcomes this study and other investigators observe (see Table 2).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, we recognize that future research needs to address challenges to the internal validity of these findings from selection bias and causal inference issues. In terms of selection bias (Newhouse & McClellan, 1998;Sturm, Unutzer, & Katon, 1999), our inability to use instrumented models in all likelihood downwardly biases the indicator-outcome relationships we report by an estimated 20% or greater (Fortney et al, 2001;Schoenbaum et al, 2002). In terms of inference, we recognize the non-experimental design prevents us from definitively concluding that high-quality depression care improves clinical outcomes; however, experimental studies showing that interventions that improve antidepressant medication management do in fact significantly reduce depressive symptoms (Wells et al, 2000;Rost, Nutting, Smith, Elliott, & Dickinson, 2002;Katon et al, 1995;Katon et al, 1996;Schulberg et al, 1996;Katzelnick et al, 2000;Katon et al, 1999;Simon, VonKorff, Rutter, & Wagner, 2000;Hunkeler et al, 2000), strengthen the causal link between quality and outcomes this study and other investigators observe (see Table 2).…”
Section: Discussionmentioning
confidence: 95%
“…To rule out the possibility that the indicator's impact on severity reflected concurrent psychotherapy, we conducted an analysis in the subgroup of patients whose administrative database records indicated they had no psychotherapy visits in the 6 months following the index visit. We were prohibited from using instrument variables to correct for selection bias by the small sample size; however, previous research suggests that non-instrumented estimates of indicator-outcome relationships are conservative (Schoenbaum et al, 2002;Fortney et al, 2001). Power analyses indicated that the sample size provided us greater than 80% power to detect a .8 effect of the indicator on severity change using a two-sided test with alpha set at .05.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence-based guidelines are available to facilitate clinical decisionmaking, and guideline-concordant treatment improves outcomes [2]. Yet despite the high prevalence of depression, its associated disability, and availability of effective treatments, only 17-36% of depressed patients receive guideline-concordant care [1-5].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] However, empirical evidence has yielded mixed results for the effectiveness of treating subthreshold depression. 10,11 The conflicting findings surrounding subthreshold depression may be partially explained by the heterogeneity of the condition being studied; many different definitions of subthreshold depression have been used in the past. 12 To standardize the assessment of subthreshold depression, the DSM-IV-TR 13 has published research criteria for the proposed diagnosis of minor depressive disorder.…”
mentioning
confidence: 99%